2004
DOI: 10.1144/16-764903-117
|View full text |Cite
|
Sign up to set email alerts
|

Laurentian provenance and an intracratonic tectonic setting for the Moine Supergroup, Scotland, constrained by detrital zircons from the Loch Eil and Glen Urquhart successions

Abstract: Detrital zircons in psammite from the type section of the Loch Eil Group of the Moine Supergroup, NW Scotland, and from an unnamed quartzose psammite, interstratified with marble, at Glen Urquhart yield similar U-Pb detrital zircon ages ranging from c. 2300 to 900 Ma. Both samples show age peaks at c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 116 publications
(175 reference statements)
4
57
0
1
Order By: Relevance
“…Stratigraphic correlations between Moine and Torridonian rocks on either side of the Moine Thrust have been suggested for a long time (Peach et al 1907;Peach and Horne 1930;Kennedy 1951;Sutton & Watson, 1964;Johnstone et al 1969;Nicholson 1993;Prave 1999) but have remained somewhat controversial (Clough in Peach et al 1910;Gibbons and Harris 1994;Stewart 2002;Friend et al2003;Cawood et al 2004). Krabbendam et al (2008) demonstrated that the lower Morar Group and Torridon Group in Ross-shire and Sutherland can be correlated on the basis of similar sedimentology, stratigraphy, detrital zircon ages and…”
Section: Stratigraphic Correlation Across the Moine Thrustmentioning
confidence: 99%
See 1 more Smart Citation
“…Stratigraphic correlations between Moine and Torridonian rocks on either side of the Moine Thrust have been suggested for a long time (Peach et al 1907;Peach and Horne 1930;Kennedy 1951;Sutton & Watson, 1964;Johnstone et al 1969;Nicholson 1993;Prave 1999) but have remained somewhat controversial (Clough in Peach et al 1910;Gibbons and Harris 1994;Stewart 2002;Friend et al2003;Cawood et al 2004). Krabbendam et al (2008) demonstrated that the lower Morar Group and Torridon Group in Ross-shire and Sutherland can be correlated on the basis of similar sedimentology, stratigraphy, detrital zircon ages and…”
Section: Stratigraphic Correlation Across the Moine Thrustmentioning
confidence: 99%
“…The detrital zircon population in the basal Rubha Guail Formation is indeed dominated by Archean zircons (Kinnaird et al 2007), similar to that of the Stoer Group (Rainbird et al 2001;Kinnaird et al 2007), reflecting proximal provenance from the nearby Lewisian gneiss. However, detrital zircons populations in the Loch na Dal and Kinloch formations are dominated by late-Palaeoproterozoic to Mesoproterozoic ages, with little or no Archaean detritus (Kinnaird et al 2007), showing similarities to detrital zircon populations in the Torridon and Moine successions (Rainbird et al 2001;Friend et al 2003;Cawood et al 2004;Kirkland et al 2008). This late-Palaeoproterozoic to Mesoproterozoic detritus is clearly distal rather than proximal, reflecting a very different source region than that of the Stoer Group; this is substantiated by the record of distal (exotic) porphyry and rhyolite clasts from higher parts of the Sleat Group (Stewart 2002).…”
Section: Stratigraphic Correlation Across the Moine Thrustmentioning
confidence: 99%
“…1a; Dalziel & Soper 2001). Partly, on the basis of detrital zircon data, Cawood et al (2004) suggested an intracratonic setting. Krabbendam et al (2008), while working in the lowermost Morar Group, documented fluvial braidplain deposits similar to the Torridon Group farther west, and suggested molasse-type deposition in a foreland basin to the Grenville Orogen.…”
mentioning
confidence: 99%
“…Eriksson et al 2001). Over the last decades, the 43 application of detrital zircon dating has provided a means to constrain the maximum 44 age of deposition and the provenance of the detritus of such sequences (Froude et al 45 1983; Nelson 2001; Cawood et al 2004) and the database of such dates is growing 46 fast (e.g. Cawood et al 2007).…”
mentioning
confidence: 99%